Modern therapeutic potential of super-selective β1-adrenoblocker nebivolol - V. I. Makolkin; D. A. Napalkov (Кардиоваскулярная терапия и профилактика, 1970)
Beta-adrenoblockers, included in any cardiovascular disease treatment standard, became a key part of clinical practice only in late XX century. Nebivolol is a highly selective beta-1 -adrenoiblocker, modulating endothelial NO release and subsequent physiological vasodilatation. Nebivolol has multiple clinical indications, including coronary heart disease, arterial hypertension, and chronic heart failure. Due to its super-selectivity it can also be beneficial in patients with diabetes mellitus, chronic obstructive pulmonary disease, and erectile dysfunction.